Betaine as stimulant to promote feed intake of Grouper on partial plant-based diets - Gunzo Kawamura (Universiti Malaysia Sabah, 2014)
Behavioural assays with video recording and an 8-week feeding trial were conducted to determine the taste effects of betaine and its potential to improve the intake of soybean meal-based diet in the juvenile grouper, Epinephelus fuscoguttatus. In the behavioural assays, agar gel pellet was used as the medium to deliver the chemical test substances - betaine (BET), amino acids mixture (AAM), and mixtures of 1: 1,1: 2,1: 3,1: 4,1: 5 BET+AAM to the fish. The pure agar gel (PAG) and feed extract (FE) pellets were used as the negative- and positive-control, respectively. From the recorded videos, two parameters were observed: (I) the pellet was consumed or rejected [A] - if consumed, recorded 1; if rejected, recorded 0, and (II) frequency of the pellet been captured before it was consumed or rejected and ignored [B], and the preference index was calculated through [A] /[B]. The PAG pellet was totally rejected by the fish (index's value = 0). The index's values of BET and AAM were 0.17 f 0.39 and 0.19 ± 0.31 (mean ± SD), respectively. No significant difference was found among the index's values of PAG, BET and AAM pellets. However, the index's values of all BET+AAM pellets (1: 1- 1: 5) were very high (0.60 - 0.90), and were significantly higher than those of the PAG, BET and AAM pellets. No significant difference was found among the index's value of 1: 1, 1: 2,1: 3, and 1: 4 BET+AAM treatments. These results concluded that betaine is a feed enhancer for the E. fuscoguttatus and little amount of betaine supplementation is sufficient to enhance the flavour of amino acids mixture. In the feeding trial, 5 experimental diets were prepared: 1) Control - fish meal based diet, 2) SBM40 - 40% of fish meal protein replaced with soybean meal protein, 3) BET05,4) BET10, 5) BET15 - SBM40 supplemented with 0.5%, 1.0% and 1.5% of betaine, respectively, and each diet was fed to triplicate groups of fish. In general, the fish fed betaine supplemented diets (BET05, BET10, and BET15) attained better growth performance and feed utilization than those fed SBM40, although the fish fed Control diet achieves the best performance. Among the betaine supplemented diets, fish fed BET10 attained the highest feed intake, weight gain and survival, although no significant difference was found. Therefore, it was concluded that dietary betaine supplementation can improve the intake of soybean-meal-based diet in the juvenile grouper, and the optimum supplementation level of betaine was 1%